Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11262-007-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of African horse sickness virus VP7 protein expression in cultured cells by RNA interference

Abstract: RNA interference (RNAi) is the process by which double-stranded RNA directs sequence-specific degradation of homologous mRNA. Short interfering RNAs (siRNAs) are the mediators of RNAi and represent powerful tools to silence gene expression in mammalian cells including genes of viral origin. In this study, we applied siRNAs targeting the VP7 gene of African horse sickness virus (AHSV) that encodes a structural protein required for stable capsid assembly. Using a VP7 expression reporter plasmid and an in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Moreover, clinical trials in humans were started using siRNA in the treatment of respiratory syncytial virus (RSV) infections (Haasnoot et al, 2007). For equine viruses, in vitro studies have shown that siRNA can reduce viral titers in cell cultures infected with equine arteritis virus (Heinrich et al, 2009), African horse sickness virus (Stassen et al, 2007) or Venezuelan equine encephalitis virus (O'Brien, 2007). More specifically for EHV-1, RNA interference has been effective both in vitro and in vivo, as assessed by a reduction in plaque formation in cell cultures and a reduction in clinical signs (weight loss) and viral replication within lung tissue in a murine model of EHV-1 infection (Fulton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical trials in humans were started using siRNA in the treatment of respiratory syncytial virus (RSV) infections (Haasnoot et al, 2007). For equine viruses, in vitro studies have shown that siRNA can reduce viral titers in cell cultures infected with equine arteritis virus (Heinrich et al, 2009), African horse sickness virus (Stassen et al, 2007) or Venezuelan equine encephalitis virus (O'Brien, 2007). More specifically for EHV-1, RNA interference has been effective both in vitro and in vivo, as assessed by a reduction in plaque formation in cell cultures and a reduction in clinical signs (weight loss) and viral replication within lung tissue in a murine model of EHV-1 infection (Fulton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the method could be significantly improved by reducing this virus background with discriminating specific siRNAs. Very strong reduction of virus growth has been published for African horse sickness virus, another serogroup of the genus O rbivirus [20]. On the other hand, the amount of in vitro synthesized RNA in infected cells could be further increased to improve the efficiency to rescue reassortants.…”
Section: Resultsmentioning
confidence: 99%